FAKTOR-FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PENDAPATAN USAHATANI BAWANG MERAH DI DESA TORONGREJO KOTA BATU - Erika Chindy Fitta Sari; Masyhuri Mahfudz; Farida Syakir (Program Studi Agribisnis, 2019)
AbstractThe purpose of this study was to determine the cost, revenue, income and R / C ratio and to find out how the influence of socio-economic factors on the income of onion farming in the study area. The research approach was obtained from data directly from red onion farmers in Torongrejo Village, Junrejo District, Batu City. The sampling method is done in a simple random sample and Slovin calculation. The analytical method used is the R / C ratio and the cobb-douglass income function.Based on the results of the analysis carried out obtained an average cost of Rp. 18,087,290 / Ha / MT, receipt of Rp. 28,824,000 / Ha / MT, income of Rp. 10,736,706 / Ha / MT and R / C ratio of 1.6. Based on the analysis of Cobb Douglass's income function which has a significant effect on socio-economic factors that affect the income of onion farming, namely age and cost with a probability value of less than 0.05.Keywoard : Factors socio economic, revenue